Review of the cicada genus Platylomia Stål (Hemiptera, Cicadidae) from China, with description and bioacoustics of a new species from Mts. Qinling - Wang, Xu; Wei, Cong (Zootaxa, 2014)
The species of Platylomia Stål from China are reviewed and a new species, P. shaanxiensis sp. n., from Shaanxi, China is described. Acoustic signals produced by males of this new species were recorded and analyzed. P. juno Distant is transferred to the genus Macrosemia. A key to the species of Platylomia from China is provided.